An analysis of the delivery of anaesthetic training sessions in the United Kingdom1. (6th June 2017) - Green, A.; Tatham, K. C.; Yentis, S. M.; Wilson, J.; Cox, M.
Summary: We analysed data from the electronic rota system CLWRota, covering 2, 689, 962 anaesthetic sessions between 01/01/2014 and 31/12/2015, in 91 UK Trusts, in order to investigate trainees' supervision. There were 8209 trainee attachments analysed, during which 618, 695 sessions were undertaken by trainees. The number of supervised sessions per week that trainees worked varied considerably (median (IQR [range]) 2.6 (1.6–3.6 [0–10]) for all grades combined), with senior trainees more likely than junior trainees to be supervised for fewer than the three sessions per week mandated by the Royal College of Anaesthetists. The number of supervised sessions was unrelated to Trusts' size, suggesting that trainees in smaller hospitals receive the same level of supervision as in larger teaching hospitals. Analysis of a dataset of this size should be a good reflection of the delivery of anaesthesia training in the UK.